PITAMAHA: MIMICRY IN ARTS AND DESIGN DURING THE COLONIAL ERA - Supir, I Ketut; Atmadja, Nengah Bawa; Mudana, I Gede (E-Jurnal Kajian Budaya (Online Journal of Cultural Studies), 2016)
During the pre-colonial era the Balinese arts and design were dominated by the themes of puppetry which contained the Hindu religious teachings. When the Dutch colonial government controlled Bali, the Balinese arts and design changed. This present study is intended to explore the existence of the Pitamaha association and the attitude of the Pitamaha painters towards the domination of the modern arts and design taught by Spies and Bonnet. The qualitative method and the postcolonial theory combined with various other critical supporting theories were used in the present study. The result of the study shows that Pitamaha is the first modern association of arts in Bali. However, Pitamaha still integrated the pattern of the Balinese traditional association. In this association, the royal elites were involved as the mediators between Spies and Bonnet and the Balinese painters. Spies and Bonnet taught the modern arts which were different from and even contrasted with the Balinese arts and design. However, the Pitamaha painters welcome it. This could not be separated from the practice of teaching through hegemony and domination which contrasted with what had been desired by the Balinese painters who intended to maintain the Balinese arts and design. In such an ambivalent condition, they mimed the modern arts and design. The mimicry made was not intended to mime the modern arts and design; instead, the mimicry made was intended to interpret with reference to the norms of the Balinese arts and design.
Keywords: Pitamaha, mimicry, arts and design, colonial era.